Oxford handbook of psychiatry - Semple, David (David M.); Smyth, Roger ([Oxford] : Oxford University Press, 2019)
This fourth edition of what has become an indispensable pocket guide to general psychiatry and the subspecialties continues to provide portable reassurance to health professionals at all levels of experience when dealing with psychiatric issues. As well as a comprehensive overview of the common presentations in psychiatry, this handbook includes practical guidance on the principles of management for individual conditions. Subspecialties, including old age psychiatry, substance misuse, child and adolescent psychiatry, forensic psychiatry, intellectual disability, liaison psychiatry, and psychotherapy are covered in separate chapters, as are overarching considerations such as legal issues, cultural context, and therapeutics.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 3, 2019).
Keywords: Psychiatry